EVALUATION OF THE USE OF GLYCERIN AND SODIUM SILICATE IN WATER-BASED DRILLING FLUID - Ribeiro Filho, Francisco de A.; Mainier, Fernando B.; Monteiro, Luciane P. Costa (International Journal of Research -GRANTHAALAYAH, 2020)
Glycerin is a by-product of the transesterification reaction of vegetable oil to produce biodiesel. Glycerin production has increased as the number of biodiesel industries has grown. With features such as water solubility, low cost, and non-toxicity, it is a good substance for water-based drilling fluid formulations with less environmental contamination. The experiments were conducted using a drilling fluid commonly used in Brazil and were compared with glycerin additions at concentrations of 5, 10, 15, and 20% by volume. Considering that as a result of the raw materials used, the biodiesel production routes produce a contaminated glycerin, it was decided to use a bi-distilled glycerin. In addition, sodium silicate, which uses industrial water or seawater, was added as a corrosion inhibitor due to its good performance and environmental non-toxicity. The sodium silicate was effective in combating corrosion without interfering with the fluid properties. The values of plastic viscosity, yield point, L3 (reading 3 rpm), and gel strength, mostly presented results equal to or better than the original formulation of the fluid used as a comparison.